Penghapusan Kebijakan Denda Keterlambatan pada Pembiayaan Bermasalah PT Bank BNI Syariah - Nasir, Laode Arahman; Wasilah, Wasilah (Universitas Agung Podomoro, 2018)
This study aims to analyze the policy of late charge elimination applied to PT Bank BNI Syariah. Thispolicy was initiated at the year of 2016 which predictably lead to the inclination of problematicfinancing at BNI Syariah. This study provides evaluation and recommendation for policyimplementation to reduce the number of problematic financing. This study uses qualitative methodswith a case study approach. The research instrument used was through the interview process with BNISyariah and the DSN (Dewan Syari‟ah Nasional/ Read: National Board of Islamic Law) of MUI(Majelis Ulama Indonesia/ Read: Indonesian Muslim Scholars Council). The results of the studyreveals that the application of a fine-elimination policy was applied because of bank doubts about theapplication of fines to sharia and fines that have no effect on the bank’s income. PT Bank BNI Syariahuses persuasive policies and still applies the ta'widh policy after the application of the fine iseliminated. This policy has a positive impact on marketing but is still vulnerable to an increase in thelevel of Non Performing Financing (NPF).